The Impact of Food Social Assistance on Household Food Security In An Islamic Perspective - Rahmah, Annisa; Fitri, Cut Dian; Ariyati, Nadlia (Golden Ratio of Data in Summary, 2025)
Indonesia, a developing nation, boasts a vast population of 263 million individuals. Despite this, many of the population still live in impoverished conditions, leading to a notable unemployment rate of 14.23% in Aceh, equivalent to 804,530 individuals. The Central Statistics Agency (BPS) suggests that community welfare can be gauged by food sufficiency, encompassing calorie and protein intake. This research uses logistic regression analysis to examine the determinants of food security at the household level. Logistic regression was chosen due to the categorical nature of the variables under study, specifically the classification of food security (0) and food insecurity (1). The independent variables considered in this research comprise the frequency of aid (X1), household head income (X2), family size (X3), aid amount (X4), and household perceptions of food assistance (X5). The findings reveal that the household's perception of food assistance is the most influential factor affecting household food security in Gampong Klieng Manyang. The resulting logistic regression model is represented as g(x) = -15.299 – 18.879 X1 – 0.000 X2 – 0.238 X3 – 18.460 X4 + 0.425 X5. In logistic regression, the coefficients are interpreted through odds ratios. Notably, the frequency of the aid variable exhibits the highest odds ratio, underscoring its significance in shaping household food security in Gampong Klieng Manyang, Sukamakmur District, Aceh Besar Regency.